A Short History of the Ukrainian Canadian Research and Documentation Centre on the Fortieth Anniversary of Its Founding - Stech, Zorian (East/West)

(untitled) (Canadian Institute of Ukrainian Studies University of Alberta, 2023)
This essay examines the history of the Ukrainian Canadian Research and Documentation Centre (UCRDC) in Toronto, looking at how the tragedy of the Holodomor led Ukrainian-Canadians to come together in speaking out against the Soviet regime and equally, reaffirming Ukrainian nationality on the world stage. It also examines how the UCRDC evolved from mainly studying the Holodomor to exploring other topics of interest to Ukrainians worldwide. Through filmmaking, archival development, and publications, the UCRDC has worked in ensuring that the voices of Ukraine and Ukrainians be heard.